Nursing Adolescents and Young Adults with Cancer Developing Knowledge, Competence and Best Practice (Springer International Publishing, 2018)
This book describes and explains how caring for adolescents and young adults with cancer (AYA) has developed into what is now a recognized and distinct field of nursing practice. It captures current innovative nursing practices and interventions which have developed over the past 25 years across the globe and are supported by research and evidence achieved in many European and international oncology settings. By outlining and describing educational needs of the AYA cancer nursing profession, this book supports its education and professional development for the nursing profession and serves to develop and disseminate nurses' competencies worldwide. During the last decade, AYA have gained increased attention in healthcare. Today, it is recognized that AYA with cancer have distinct needs that are different to both children and older adults. Young people are in a unique developmental and transitional phase of their lives; thus, their treatment, perspectives and experie nces have been addressed in research and the body of knowledge is growing accordingly. Some books are available that describe AYA cancer care, service delivery and aspects of age appropriate care but this volume will be the first to focus on how nurses contribute to AYA cancer care in practice. It will appeal to the AYA clinical nurses in cancer care, as well as to multidisciplinary healthcare professionals and healthcare professionals who support formal nursing education programmes, training and development in practice.